2008
DOI: 10.1103/physrevd.78.061901
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the geometric tachyon

Abstract: The motion of a Dp-brane in the background of a stack of coincident NS5-branes is analyzed as the motion of a relativistic point particle in the transverse space of the five-branes. In this system, the particle experiences a proper acceleration orthogonal to its proper velocity due to the background dilaton field which changes the dynamics from that of a simple geodesic motion. In particular, we show that in the vicinity of the five-branes, it is this acceleration which is responsible for modifying the motion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…. , 9 and G AB and B AB are the metric and the B-field in ten dimensions, given in (28). We are interested in the case when the fields representing the position of the Dp-brane X m , m = 6, .…”
Section: Dp-brane Motion In Ns5-brane Backgroundmentioning
confidence: 99%
“…. , 9 and G AB and B AB are the metric and the B-field in ten dimensions, given in (28). We are interested in the case when the fields representing the position of the Dp-brane X m , m = 6, .…”
Section: Dp-brane Motion In Ns5-brane Backgroundmentioning
confidence: 99%
“…In an attempt to understand the origin of this geometric tachyon in [17] the time dependent dynamics of probe D-brane in the background of NS5-brane was explained in terms of proper acceleration. It was proposed that the tachyonic instability is due to the geodesic deviation caused by proper acceleration (which is formed due to the background dilaton field).…”
mentioning
confidence: 99%
“…In this system, the particle experiences a proper acceleration orthogonal to its proper velocity due to the background dilaton field which changes the dynamics from that of a simple geodesic motion. In particular, it is shown that in the vicinity of the five-branes, it is this acceleration which is responsible for modifying the motion of the radial mode to that of an inverted simple harmonic oscillator leading to the tachyonic instability [20,21].…”
Section: Introductionmentioning
confidence: 99%